MOBILITIES, SOCIAL CHANGE AND CRIME lessons from poland. - Buczkowski, Konrad; Wiktorska, Paulina (ROUTLEDGE, 2023)
This book presents a synthesis of selected trends in the dynamics and structure of crime in Poland over the past 30 years, in the context of ongoing social transformations in the wider region. The book explores the impact of the deep systemic transformation of the late 1980s and early 1990s on the phenomenon of crime, its structure and dynamics, and the policy of its control in the following decades. It also examines the impact of changes resulting from the dynamic development of Polish society in the 21stcentury in the context of global changes towards the emergence of a new form of collective life, a mobile information society based on modern technologies. The focus is primarily on those deviant behaviours that can most obviously be linked to social changes, primarily political, economic, legal, and technological. The work examines disclosed crime figures available in official statistics. It also looks to the future considering the global societal changes caused by the outbreak of the COVID-19 pandemic. Based on preliminary observations made in selected countries, the authors describe associated changes in criminal behaviour and identify some pivotal developments that may influence future trends. The book will be of interest to academics and researchers working in the areas of criminal law, criminology, sociology and criminal policy.